2015
DOI: 10.1177/0093854815570963
|View full text |Cite
|
Sign up to set email alerts
|

Race, Ethnicity, and Structural Variations in Youth Risk of Arrest

Abstract: Missing from the considerable body of literature on disproportionate minority contact is an examination of the factors that influence risk of juvenile arrest. Using the National Longitudinal Survey of Youth 1997, the author examines racial/ethnic disparities in youth arrest, net of self-reported delinquency. Drawing from research using a minority threat perspective, this study examines whether disparities are exacerbated by macro levels of the relative size of the minority population and minority economic ineq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
59
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 55 publications
8
59
2
Order By: Relevance
“…While Hispanics are often considered to be at higher risk for police contact, previous studies have been mixed, finding both positive (Vazsonyi and Chen 2010) and null (Anderson 2015; Tapia 2010) associations. Reasons for these contradictory findings remain unclear, but could be related to the fact that Hispanic ethnicity may be not be as readily discernible a characteristic as race by law enforcement officials (Tapia 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Hispanics are often considered to be at higher risk for police contact, previous studies have been mixed, finding both positive (Vazsonyi and Chen 2010) and null (Anderson 2015; Tapia 2010) associations. Reasons for these contradictory findings remain unclear, but could be related to the fact that Hispanic ethnicity may be not be as readily discernible a characteristic as race by law enforcement officials (Tapia 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest was the importance of parental and other family criminal involvement which, as the authors concluded, may point to the role of law enforcement paying more attention to families known to be involved in crime. In one of the only studies of a nationally representative sample of youths, Anderson (2015) demonstrated disproportionate rates of arrest between black and white youths, but not between Hispanic and white youths, after controlling for self-reported delinquency. The study found these disparities to be magnified in predominantly non-black communities; however, it was only able to consider a limited number of community-level and no school-level factors in its analysis.…”
Section: Introductionmentioning
confidence: 96%
“…Existing research supporting the idea that police contact can be criminogenic among nonwhite communities is predominantly qualitative (24, 30, 33, 37). Many of these studies speak to the prevalence of punitive enforcement and high levels of surveillance among nonwhite communities (38–44), particularly among nonwhite boys and young men (21, 23, 45, 46). Qualitative studies illustrate that nonwhite boys and young men experience pedestrian stops as physically invasive and abusive (20, 21, 22, 35, 36).…”
mentioning
confidence: 99%
“…Similar to other nondominant minorities (see, e.g., Andersen ; Blom & Jennissen ; Briggs et al ; Bui ; Hilton ; Marshall ; McNulty & Bellair ; Peterson ; Veen et al ), Israeli‐Arabs are overrepresented in the criminal enforcement system compared to their relative size in the population. For instance, in 2014, the rate of adults convicted of all types of offenses per 1,000 residents was 10.3 for Israeli‐Arabs and 4.1 for Jews (Central Bureau of Statistics ).…”
Section: Israeli‐arabs and The Criminal Justice Systemmentioning
confidence: 74%